The role of professional calling and student cyberbullying on teachers’ presenteeism and productivity loss - Ferreira, A. I.; Almeida, I. T. R. de.; Ferreira, P. A. N. da C.; Pereira, N.; Simão, A. M. V.; Pinto, A. M.; Barros, A. (Computers in Human Behavior Reports, 2024)
The teaching profession has always been recognized as one that requires a greater vocational calling. However, education professionals have had to adapt to and manage phenomenons which have arisen due to more demanding work contexts that require them to participate in work, even when they are ill (presenteeism), and to a global-wide digital transformation. Such phenomenons include cyberbullying, which has proliferated in school environments. It is crucial to understand the impact this type of phenomenon can have on these professionals. Accordingly, the main objective of this study was to identify the needs felt by teachers to deal effectively with incidents of cyberbullying and its potential impact on and reduce presenteeism. Two studies were developed, with the intention that the hypotheses posed by the quantitative study could be enriched with the inferences drawn from the qualitative study. A sample of 542 middle school teachers responded to questionnaires and 63 participated in interviews. The results showed that teachers’ professional calling led to a lower loss of productivity, due to a lower frequency of presenteeism. This effect was more pronounced in the presence of cyberbullying observation. This study provides a contribution to the calling and presenteeism literature since it focuses on the impact of observing cyberbullying on sickness presence. It is relevant because by knowing the demands that teachers feel and the resources they lack, it is possible to implement tailored intervention and prevention programs to help professionals deal with cyberbullying.